OPTIMALISASI PERAN PEREMPUAN BERBASIS MODAL SOSIAL PADA SEKTOR PEMERINTAHAN DESA (Study pada Pengelolaan Dana Desa) - Titi Darmi (Universitas Andalas, 2016)
AbstraksThe third Nawa Cita of Presiden Jokowi is build Indonesia on the outskirts, it is meaningful that national development focused on villages oriented throughout Indonesia, so that Indonesian villages become self-sufficient village and competitiveness. Nawa cita is an orientatation of the national development planning 2012 -2019. The government has budgeted rural development on average earn 800 - 1M rupiahs for every village in accordance with the Act mandates. Based on the findings of the Coruption Eradication Commission of RI occur irregularities in the management of the Village Fund (Dana Desa/DD), including the use of DD does not correspond to the needs of the community. DD management principle is transparent and acomodate public participation, however it has not been made by manager DD. Women's participation and transparency for the public should be rise the public trust in the village officials in managing the funds of the village, however it never been taken. Role of women in planning the work program of the village called APBDes, can filter aspirations in accordance with the needs of society based on values, norms and culture. By optimizing the women role can capture the aspirations of society and openness in the management of the fund that all can be used as social capital village to village governance in the management of DD. Social capital will make the villagers and village officials have a strong bond, mutual trust, to avoid a conflict so as a valuable capital to build and boost the economy in the village.AbstraksThe third Nawa Cita of Presiden Jokowi is build Indonesia on the outskirts, it is meaningful that national development focused on villages oriented throughout Indonesia, so that Indonesian villages become self-sufficient village and competitiveness. Nawa cita is an orientatation of the national development planning 2012 -2019. The government has budgeted rural development on average earn 800 - 1M rupiahs for every village in accordance with the Act mandates. Based on the findings of the Coruption Eradication Commission of RI occur irregularities in the management of the Village Fund (Dana Desa/DD), including the use of DD does not correspond to the needs of the community. DD management principle is transparent and acomodate public participation, however it has not been made by manager DD. Women's participation and transparency for the public should be rise the public trust in the village officials in managing the funds of the village, however it never been taken. Role of women in planning the work program of the village called APBDes, can filter aspirations in accordance with the needs of society based on values, norms and culture. By optimizing the women role can capture the aspirations of society and openness in the management of the fund that all can be used as social capital village to village governance in the management of DD. Social capital will make the villagers and village officials have a strong bond, mutual trust, to avoid a conflict so as a valuable capital to build and boost the economy in the village.Keyword : woman's role, social capital, village fund (Dana Desa/DD) management.